Inaccurate level of intervertebral space estimated by palpation: The ultrasonic revelation - L H Parate; B Manjunath; C A Tejesh; V Pujari (Saudi Journal of Anaesthesia, 2016)
Background: Spinal cord injury resulting from spinal anesthesia is a rare, but an alarming scenario. The most likely cause is believed to be misjudged level of intervertebral space (IVS). We evaluated the accuracy of palpation method to locate IVS with the ultrasonography. Materials and Methods: A total of 109 patients undergoing spinal anesthesia were included in this observational, double-blind study. First anesthesiologist was asked to mark IVS using palpation method. It was followed by ultrasonographic assessment by another anesthesiologist who was unaware of the level estimated for the mark. We evaluated the accuracy of palpation method in sitting and lateral position as well as the impact of the anesthesiologist′s experience (Trainee/Consultant). Statistical Analysis Used: Association between the gender, anthropometric parameters, type of anesthesiologists assessing the IVS, and the level of agreement were identified using Chi-square test. The agreement between palpation method and ultrasound assessment of IVS was analyzed using kappa statistic. P < 0.05 was defined as statistical significance. Results: The IVS located by palpation method was in agreement with ultrasound location in 37.14% of the patients. There were no statistically significant differences found in terms of demographic data (sex, age, height, weight, or body mass index [BMI]) between agreement and disagreement group. The rate of errors was found to be significantly higher (P = 0.01) among the trainees (74.51%) than the consultants (51.86%). The rate of errors was not different between the sitting and lateral position. The frequency of errors was more common in cephalad direction (53.31.5%) compared to caudal direction (9.52%). The misidentified spaces were as high as three spaces above the intended space while in caudal direction it differed by only one space. Conclusion: The accuracy of palpation method controlled by ultrasound is 37.14% and differs by 1-3 IVS in cephalad direction (53.31%). The accuracy is affected by anesthesiologist′s experience but remains unaffected by age, sex height, BMI, and patient positioning.